Leader-Member Exchange: an Integrated Conceptual Model Study of Antecedents and Outcomes Variables in the Social Exchange Perspectives - Waskito, Jati; Riani, Asri Laksmi; Suyono, Joko; Setiawan, Ahmad Ikhwan (Universitas Muhammadiyah Surakarta, 2018)
This study develops and tests integrated models of the antecedents and consequences of LMX, based on social exchange theory. The survey was carried out by taking samples of paramedics in Yogyakarta. Results indicate that LMX have unique antecedents (liking, expectations, and Dyad tenure) and outcomes (favor doing, OCB, and performance rating)